A Language-Independent Measurement of Economic Policy Uncertainty in Eastern European Countries. Issue 5 (8th April 2020) - Kupfer, Alexander; Zorn, Josef
ABSTRACT: This article proposes a novel way to construct an index for economic policy uncertainty that does not depend on language proficiency. We use two specific features of search volume extraction on Google Trends, combine policy-relevant search queries, and construct our Google economic policy uncertainty index for nine Eastern European countries—a region in which the construction of other economic policy uncertainty indices would require good language proficiency. We illustratively show that major policy-related events are captured and find that shocks on economic policy uncertainty yield a sizable impact on macroeconomic variables.